Participatory Culture in Indonesian Communities: A Study of #Gerakbersama Campaign - Mia Angeline; Yuanita Safitri (Bina Nusantara University, 2018)
The research aimed to provide an overview on how digital conversation and participatory culture processes take place in Indonesian communities in #GerakBersama campaign. This research used a qualitative approach with case study methods. The results show that digital conversations in the #GerakBersama campaign are mostly triggered by content shared by the initiators. However, most accounts who share the content or hashtags in social media are organizations. In short, the digital conversation of this campaign is still a one-way conversation from the initiators to the public. In #GerakBersama campaign, the process of forming participatory culture begins with the existence of a society that has the same concern and a feeling of disgust about violence against women. The existence of this similarity is also reinforced by the characteristics of new media which allows users to share and create participatory culture.